The market risk premium in Iceland : what is the market risk premium for the Nasdaq OMX Iceland? - Kristján Jóhannesson 1990- (2019)
Market risk premium (MRP) is a key component in the cost of equity estimation. In foreign equity markets there have been a number of studies on the different types of the MRP. In Iceland the MRP has not been studied to the same extent. The studies that have been performed on the Icelandic market have been affected by the bubble phase period, 2004-20017, that ended with the collapse of the financial sector in 2008. That is why the focus in this research is going to be on the time period from 2010. The aim of this research is to determine the MRP for the Icelandic market. The following questions are going to be answered to determine the range of the MRP. 1. What is the historical MRP for the Icelandic market for the time period 2010 - 1st quarter 2019? 2. What is the implied MRP for the Icelandic market for the time period 2010 - 1st quarter 2019? 3. Are these estimates consistent with the MRP used by Icelandic market practitioners and MRP in other markets? The historical MRP was estimated using the OMXIGI index as a benchmark for the market returns. The proxy for the risk-free rate was the OMXI5/10YNI index. The geometric average is 6.72%. The standard error of the historical MRP is 4.13%. The implied MRP was estimated using three different methods: The discounted cash flow method on dividend yield and buyback yield for 2019, resulting in an implied MRP of 3.73%. Using country risk premium to estimate the range of the MRP in Iceland, using data from multiple markets, the range is 5.13% - 6.79%. The risk premium factor model was also implemented using the P/E ratio of the OMXI6/8 index. Resulting in an implied MRP of 6.08%. The result from the interviews are that CAPM is the preferred model to estimate the cost of equity. The range of the MRP between the interviewees is from 5% to 6.7%. Keywords: Cost of Equity, Market Risk Premium, Historical market risk premium, Implied Market Risk Premium, Risk Premium Factor, Iceland.